Industrial Applications for Intelligent Polymers and Coatings 2016
DOI: 10.1007/978-3-319-26893-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Polymers and Coatings

Abstract: Electroactive polymers (EAPs) and coatings (EACs) provide an expanding and progressive frontier for responsive drug delivery and the design of biomedical devices. EAPs possess the distinctive propensity to undergo a change in shape and/or size following electrical current activation. Current interest in EAPs and EACs extends to use in controlled drug delivery applications, where an "on-off" mechanism for drug releases would be optimal, as well as application in a biomedical devices and implants. This chapter e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…The ease and flexibility of synthesizing polypyrrole in mass at ambient temperature in many solvents, including water is the reason for its availability [35][36][37][38]. equipment, computer displays, biosensors, blood conduits, drug delivery system, neural probes, and as a biological material in neural tissue engineering [43][44][45][46][47].…”
Section: Polypyrrolementioning
confidence: 99%
“…The ease and flexibility of synthesizing polypyrrole in mass at ambient temperature in many solvents, including water is the reason for its availability [35][36][37][38]. equipment, computer displays, biosensors, blood conduits, drug delivery system, neural probes, and as a biological material in neural tissue engineering [43][44][45][46][47].…”
Section: Polypyrrolementioning
confidence: 99%
“…Advancement of effective and powerful mechanisms and devices that are actuated by EAP materials needs enhanced understanding of their behaviour, design concepts for efficient actuation, generation and sensing and reliable and repeatable fabrication and characterization methods, as well as effective control algorithms and electronics (Bar-Cohen, 2017; Bundhoo, 2009; Kaasik et al, 2017; Mengmeng et al, 2017; Rus and Tolley, 2015; Wang et al, 2016; Wilson et al, 2007). The current accomplishments and challenges in the field of EAP are noteworthy (Asaka and Nakamura, 2014; Biggs et al, 2013; du Toit et al, 2016; Vinogradov et al, 2005). Kaneto (2016) has shown that the research trends of EAPs and conducting polymers characteristics as given in Table 4.…”
Section: Recent Trends and Advancementmentioning
confidence: 99%
“…Advancement of effective and powerful mechanisms and devices that are actuated by EAP materials needs enhanced understanding of their behaviour, design concepts for efficient actuation, generation and sensing and current accomplishments and challenges in the field of EAP are noteworthy (Asaka and Nakamura, 2014;Biggs et al, 2013;du Toit et al, 2016;Vinogradov et al, 2005). Kaneto (2016) has shown that the research trends of EAPs and conducting polymers characteristics as given in Table 4.…”
Section: Recent Trends and Advancementmentioning
confidence: 99%